Cubicalization of Professional Education - Anandakrishnan, M. (Journal of Engineering Education Transformations, 2010)
During the discussions in the Committee on Renovation and Rejuvenation of Higher Education Prof. Yashpal who headed the Committee coined the term 'cubicalization" to describe the state of fragmentation and isolation of professional disciplines from one another.